La legge n. 219/2017 su consenso informato e disposizioni anticipate di trattamento: il problema e le risposte della legge - Nicolussi, Andrea (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
The Author addresses the new Italian Law regarding informed consent and advanced directives and the main issues raised. Firstly, the author stresses the general idea that the Law provides an answer to the question deriving from the pervasive presence of techniques in medical treatments. From this point of view, informed consent can be thought of as a means for adapting the treatment to the person in line with the principle of respect for the person (Art. 32 of the Italian Constitution) and thus avoiding a sense of imprisonment. Respect for the person implies a special care and not indifference, so that consent implies the due engagement of the person in the decision process as the very etymology of the word con-sent suggests. Respect for a person certainly means respect for his or her autonomy, but the former concept does not correspond necessarily with the latter, especially if autonomy is not interpreted within a framework of solidarity. Informed consent also implies a new conceptual frame of reference, in which arrangements between patients and physicians must be fully understood. In fact, they are different from a contract and require a new thinking. Regarding the role of physicians, the author points out that the Law avoids rendering physicians mere executors of orders and that the reference to the deontological code must be taken seriously. Concerning advanced directives, their bindingness and the role of the proxy are evaluated as well as the questions relating to surrogate decisions and advanced care planning. Finally, some remarks are addressed to the decision making process when treatments of minors are at issue. Keywords: Informed consent; Advance directives; Proxy; Therapeutic arrangements; Withdrawal.